2019
DOI: 10.1177/2165079919843306
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Level of Casting Factory Workers and Its Relationship With Occupational Health and Safety Training

Abstract: Health literacy (HL) is a stronger predictor of an individual’s health status than income, employment status, education level, and race or ethnicity. Lower levels of HL may contribute to low uptake or less adherence to occupational health and safety (OHS) training. This study was conducted among casting factory workers who received OHS training routinely. Data on sociodemographic characteristics, OHS training, and scores of the Health Literacy Survey–European Union (HLS-EU) were collected. Of the 282 of the 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…The various measures of outcomes in intervention studies promoting individual work-related or occupational health literacy ( Table 3 ), and the measurement instruments available to date ( Table 4 ) indicate a need for validated measurement instruments designed for the workplace context. Because no specific measurement instrument was available, in an intervention study among casting factory workers, general health literacy was measured and linked to workers’ perceptions of occupational health and safety training [ 14 ]. Suthakorn et al [ 69 ] recommend the development of occupational health literacy measurement instruments tailored to specific work settings in different cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The various measures of outcomes in intervention studies promoting individual work-related or occupational health literacy ( Table 3 ), and the measurement instruments available to date ( Table 4 ) indicate a need for validated measurement instruments designed for the workplace context. Because no specific measurement instrument was available, in an intervention study among casting factory workers, general health literacy was measured and linked to workers’ perceptions of occupational health and safety training [ 14 ]. Suthakorn et al [ 69 ] recommend the development of occupational health literacy measurement instruments tailored to specific work settings in different cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals' health-related decisions based on relevant information can also be beneficial in the context of work and health, such as in questions regarding recovery after illness, sickness absence, and rehabilitation [13] back into community and working life. Limited health literacy among employees can also be one of the factors limiting the understanding and training effectiveness of occupational health and safety [14]. In occupational settings, health literacy can be allocated to these two components of workplace health management in Germany: "occupational health and safety" as well as "workplace health promotion" [4]; however, especially with regard to longer working lives and the blurring of work and other areas of life, employees' own contributions to maintaining their work ability are becoming increasingly important in order to ensure that the living and working conditions of employees are safe and healthy [4].…”
Section: Health Literacy In the Context Of Employmentmentioning
confidence: 99%
“…For example, a study involving 282 workers at a factory who received the OHS training routinely showed that 13.5% had inadequate, 47.5% problematic, 30.9% sufficient, and 8.2% excellent HL scores. (6) There was also a study conducted on 421 farmers working in Thailand, which reported that the farmers' mean HL level was found to be 34.98 (SD=6.87) points over a range of 0-50 points. (7) Recently, 686 university students were evaluated for HL status by Gamsýzkan et al, who found that 21.1% (n=145) of the students had inadequate HL, 41.8% (n = 287) had limited HL, 30.9% (n=212) sufficient, and 6.1% (n=42) excellent HL.…”
Section: Introductionmentioning
confidence: 98%
“…Individuals with good health literacy have a better understanding of their health and are likely to have good health outcomes [8]. Among the health determinants such as income, employment status, and education level, health literacy is one of the most signi cant determinant of an individual's health status [9]. Therefore, health care professionals require health literacy skills because they have the responsibilities to assist the patients develop health literacy skills [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence strongly suggest that health literacy level is generally low globally and is cause for concern for health care authorities [1,9]. The responsibility of improving health literacy among individuals lies with health care workers, with nurses having a role of educating patients and the community on health literacy and practices [8,16].…”
Section: Introductionmentioning
confidence: 99%